HOLD HEADING POSITION SYSTEM OF UNDERWATER REMOTELY OPERATED VEHICLE BASED ON PID - Parama Diptya Widayaka; Akbar Sujiwa (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
Underwater remotely operated vehicle mainly used to help human for underwater activities such as underwater exploration, underwater maintenance, and underwater search and rescue. Underwater remotely operated vehicle also used for education, entertainment, and competitions. In some case especially for an important or highly risk tasks, the ROV applied some functions to improve and optimize the use of the ROV for some missions. This paper presents a heading hold system which is applied in the ROV to maintain heading position or pose of the robot. Using a GY-271 compass sensor to read the data of ROV heading position, microcontroller Arduino mega 2560 as a central processing unit and PID controller as a feedback controller to maintain ROV on desired position by controlling thruster speed and direction. The experiments give a result of the control system using PID by 5% error for the ROV to maintain heading position in steady position.